Induced hypotension for functional endoscopic sinus surgery: comparison between dexmedetomidine and nitro-glycerine - A. A., Habib Rahaman; S. M., Dhananjaya Kumar; N., Amulya; M., Geetanjali; O., Kiran Kumar (International Journal of Research in Medical Sciences, 2022)
Background: Functional endoscopic sinus surgery (FESS) is a minimally invasive technique used to restore sinus ventilation and normal function by opening sinus air cells and ostia. FESS requires bloodless field, several techniques and drugs have been used in the past for achieving controlled hypotension such as nitroglycerine, esmolol, remifentanil, dexmedetomidine, isoflurane, propofol. Therefore, this study was conducted to compare between dexmedetomidine and nitroglycerine for controlled hypotension for FESS. Primary aim to compare quality of surgical field using average category scale and surgeon satisfaction and secondary aim to compare arterial pressure and heart rate changes between dexmedetomidine and nitroglycerine when used to induce hypotension. Methods: This study was conducted in 40 consenting adult patients posted for FESS and were randomly divided into two groups, group D received dexmedetomidine 1 mcg/kg and group N received nitroglycerine 0.5 mcg/kg/min, both infusions started 10 min after induction. Parameters such as quality of surgical field by average category scale, heart rate and mean arterial pressure (MAP) recorded every 10 minutes. Results: Dexmedetomidine and nitroglycerine both had comparable quality of surgical field. ACS grading of 1 or 2 were found among both the groups. Dexmedetomidine group had better mean arterial pressure at 10th, 20th, 30th, 40th, 50th, 60th and 70th min and heart rate at 10th, 20th, 30th, 40th, 50th, 60th and 70th min when compared to nitroglycerine group. Conclusions: Dexmedetomidine and nitroglycerine both were found to be safe to use for controlled hypotension in functional endoscopic sinus surgeries.